Diagnosis and treatment of non-infectious cystitis in domestic cats at the Hasanuddin University Veterinary Teaching Hospital, Makassar - monica, waode santa; Triwinarsih, Andi Nurabrar; Fatmawati, Dian; Ramdhani, Suci; Sinusi, Muhammad Zulfadillah; Musdalifah; Mustakdir, Zulfikri; Julyana, Andi Tri; Kajang, Elphan Augusta; Ummah, Andi Rifqatul (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2025)
Feline Lower Urinary Tract Disease (FLUTD) is a term used to describe a condition that can affect the urinary bladder and lower urinary tract. Cystitis is an inflammatory disease of the urinary bladder caused by infectious and non-infectious agents, namely urine crystals. The occurrence of crystals in the urinary tract often occurs in cats that consume high-mineral and calcium feed without adequate water intake. The cat case complained of not urinating for three days, abdominal distension, and pain in the urinary bladder. Examination methods with routine hematology, ultrasonography, native tests, urine dipsticks, bacterial cultures, and native tests were carried out at the Unhas Veterinary Teaching Hospital. The diagnosis of Cystitis was confirmed by laboratory examination results found struvite crystals found >10 crystals/HPF, ultrasound examination showed hyperechoic appearance in the urinary bladder, urine dipstick test pH 7.5 and protein +++, hematology results found an increase in MCV values ​​and a decrease in Hb, MCHC and PCT indicators. . Handling of this case with catheter installation and fluid therapy. Treatment with antibiotics, anti-inflammatories, and supportive drugs vitamins and immune boosters. Also given a diet feed to prevent recurrence of the case